Stylization – Ideas for the Reactivation of the Silesian Language - Tambor, Jolanta (Poznańskie Studia Slawistyczne, 2015)
In the article, the status of the Silesian ethnolanguage is shortly discussed. The opinions of two groups writing about this topic are presented: those writing from the perspective of the detailed linguistics (historical) and those writing from the perspective of the general linguistics. The author mentions also about the social, legal, and political background that creates the status of ethnolanguages in the contemporary political-legal situation of Europe. Basing on these, the author analyzes publications of the recent 25 years, which belong to popular scientific writings and belles-lettres. She exposes their role in raising of the prestige of the Silesian ethnolanguage.